Development of Sasak Local Wisdom Based Quality Assurance Model for Islamic Religious Education to Enhance Learning Quality in Islamic Elementary Schools - Kaharudin Kaharudin; Khoirul Anwar; Olivia Fachrunnisa (Journal of Education and Learning Sciences, 2026)
This study aims to develop a Sasak local wisdom based quality assurance model for Islamic Religious Education (IRE) to enhance learning quality in Islamic elementary schools. The study was motivated by the limited integration of local cultural values within existing educational quality assurance systems, which often emphasize administrative compliance rather than contextual learning improvement. This research employed a Research and Development (R&D) approach using the ADDIE model and a mixed-method sequential exploratory design. Qualitative data were collected through observations, interviews, documentation studies, and focus group discussions, while quantitative data were obtained through expert validation, practicality assessments, and effectiveness testing. The developed model integrates six core Sasak cultural values—besemeton, saling ajinang, bedadayan, teguq, soloh, and reme—into all stages of the quality assurance cycle, including planning, implementation, monitoring, evaluation, and continuous improvement. Expert validation results indicated a validity score of 92.4% (very valid), while practicality testing by teachers and school stakeholders achieved 89.7% (very practical). Effectiveness testing showed a significant improvement in learning quality indicators, with mean scores increasing from 74.8 before implementation to 86.3 after implementation (p < .05). The novelty of this study lies in the development of a culturally responsive quality assurance model that systematically integrates indigenous Sasak values into the Islamic Religious Education quality assurance cycle. The model contributes theoretically to educational quality management and practically provides a contextual framework for strengthening learning quality and character development in Islamic elementary schools.